The role of Triglyceride-Glucose index in predicting pre-DM risk among Chinese adults - Zhangxin Wen; Qinyi Wang; Chuo Luo; Yangna Ou; Licheng Tang; Hong Liu; Zhifeng Sheng (Scientific Reports)
Abstract The triglyceride-glucose (TyG) index, a key indicator of insulin resistance, acts as a predictive factor for diabetes; however, its potential role as a prognostic marker for prediabetes (Pre-DM) remains to be elucidated. This retrospective cohort study enrolled 100,309 Chinese adults from a hospital in China between January 2010 and December 2014. We employed Cox regression, generalized additive models (GAMs), and smooth curve fitting, supplemented by a series of sensitivity analyses, to evaluate the relationship between the TyG index and pre-DM (Pre-DM). To investigate the potential mediating effect of BMI on the association between the TyG index and Pre-DM, a mediation analysis was performed. The prevalence of Pre-DM was 12.3% over 6.0 years. After adjusting for the covariates, the results showed a positive relationship between the triglyceride-glucose (TyG) index and no pre-DM. (HR = 2.1, 95%CI 2.0-2.1). Furthermore, the TyG index level exhibited a non-linear correlation with the incidence of Pre-DM, and sensitivity analysis confirmed the robustness of these findings. Subgroup analysis revealed a more pronounced association between the TyG index and Pre-DM among females and individuals aged 60 years or younger with a body mass index (BMI) of 24 kg/m² or less. Both the TyG index and BMI level were notably correlated with Pre-DM, with BMI significantly mediating 30.7% of the relationship between the TyG index and Pre-DM. Our research confirms that the TyG index serves as an independent predictor for pre-DM among the Chinese population. The body mass index (BMI) partially mediates the correlation between the TyG index and pre-DM. It is particularly important for individuals with normal weight to pay close attention to their TyG index to prevent the progression towards pre-DM.